Peran Pendidikan Agama Islam dengan Pendekatan Ilmu Al-Qur'an dalam Membangun Karakter Kepemimpinan Siswa - Mohammad Firmansyah; Naily An Ngimatul Azka; Raudya Nurafifah; Muzawir Munawarsyah (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
This study aims to analyze various sources of literature to understand how Islamic religious education, through the perspective of the Qur'an, can contribute to the formation of student leadership character. The method used is a literature study or also known as a literature review sourced from previous studies and reading books. The data used are document data, both from the Qur'an, Al-Hadith, textbooks, scientific journals, and other relevant document sources. The data were analyzed descriptively by collecting data from various articles and books, then analyzed to draw conclusions. The study shows that Islamic leadership education has a positive impact on the development of student character, increasing attitudes of responsibility, honesty, and the ability to work together. Students involved in extracurricular activities show increased communication skills and self-confidence, are able to apply Islamic values ​​in various situations. Effective character education can improve the quality of students' attitudes and behavior, in line with the finding that religious-based leadership education has a positive effect on the development of student character.